Key German Cartels under the Nazi Regime - Newman, Philip C. (Quarterly Journal of Economics, 1948)
Introduction: impact of the Nazi economic policy on the cartels, 576. — I. Potash: early developments, 577; the 1919 legislation, 578; operations under the 1919 law, 582; the International Potash Cartel, 582; penetration of the American potash industry, 584; the Potash Cartel and Combines under the Nazi regime, 585. — II. Cement: pre-Nazi market controls, 588; early stages of Nazi control, 589; the cement industry during the war, 591; the International Cement Cartel, 594.